An updated review of the treatment landscape for advanced gastrointestinal stromal tumors. Issue 13 (11th May 2021) - Patel, Shreyaskumar R.; Reichardt, Peter
Abstract : Before the introduction of tyrosine kinase inhibitors (TKIs), the overall survival of patients with advanced or metastatic gastrointestinal stromal tumors (GISTs) was 10 to 20 months because of the lack of approved therapies. In the last 20 years, a treatment algorithm for patients with advanced GISTs, which includes imatinib, sunitinib, and regorafenib as first‐, second‐, and third‐line therapies, respectively, has been established. Recently, 2 new TKIs have been approved: ripretinib for fourth‐line therapy and avapritinib as first‐line therapy in patients harboring platelet‐derived growth factor receptor α ( PDGFRA ) exon 18 D842V mutations. Additionally, there are several experimental therapies under investigation that could advance individualized patient care. All of these therapies have varying efficacies and safety profiles that warrant an updated treatment landscape review. This review article summarizes the efficacy and safety data currently available for conventional TKIs along with recently approved and experimental therapies. Abstract : With evolving treatment options and effective toxicity management, patients with advanced gastrointestinal stromal tumors are living longer than ever before. Recently approved targeted therapies and the investigation of experimental treatment options have the potential to alter the current treatment algorithm and encourage personalized patient care.